Tembikar Song Tritis: Suatu Bukti Permukiman Berkelanjutan - Goenadi Nitihaminoto (Balai Arkeologi Yogyakarta, 2006)
This paper is compiled based on the results of research on the Song Tritis site in 2002. Research after 2002, the results are relatively the same both in type and quantity. Differences may occur in soil conditions and absolute dating. The number of soil layers will increase if the excavation is carried out deeper and the absolute date will get older, which marks the oldest life activities in the Song Tritis Site, according to the excavation capability. Thus, the oldest dating in this paper cannot represent the oldest life span at the Song Tritis Site because it is suspected that there will be an older date obtained in future studies.